Under-frequency load shedding of microgrid systems: a review. (4th July 2022) - Madiba, T.; Bansal, R.C.; Mbungu, N.T.; Bettayeb, M.; Naidoo, R.M.; Siti, M.W.
ABSTRACT: Everywhere, typical network systems are challenging two opposite situations, mainly caused by suppliers and consumers. The provision of new power quality resources and an increase in electricity consumption are the main problems in satisfying the daily need and the rising number of critical base loads. Because of the quick and unforeseen increase in consumers and failure to construct new micro-energy power plants in distribution systems in general, optimal control should be implemented to assure the distribution system's proper operation. The application of adequate computational load shedding techniques is necessary for this approach. This paper reviews microgrids' work, a considerable number of computational intelligence methods, and different classes of load shedding techniques applied to date in the distribution systems. A conclusion has been drawn given several unforeseen blackout problems occurring in major electrical distribution companies worldwide. The maximum use must be made of renewable energy resources, mainly when there are load shedding and blackout problems.